Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Mengembangkan Kecerdasan Intrapersonal dan Interpersonal Siswa di MI Hamzanwadi No. 1 Lombok Timur - Siti Fatmawati Kumala; Ahmad Nurul Kawakip; Samsul Susilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Internalization of Islamic Religious Education values plays a crucial role in shaping students' intrapersonal and interpersonal intelligence, particularly amidst the challenges of character development in the modern era. This study aims to describe the process of internalizing Islamic Religious Education values and its implications for the development of these two intelligences at MI Hamzanwadi No. 1 Pancor. The study employed a qualitative case study approach with data collection techniques through observation, interviews, and documentation. The results indicate that internalization of values occurs through teacher role models, the practice of daily worship and etiquette, the conditioning of a religious environment, and the enforcement of rules. This process impacts on increasing students' intrapersonal intelligence, such as the ability to recognize oneself, manage emotions, and build self-motivation; and interpersonal intelligence, such as the ability to communicate politely, cooperate, and empathize. Thus, internalization of Islamic Religious Education values has been proven effective in shaping students' overall character.